Consumers' Role Performance and Brand Identification: Evidence from a Survey and a Longitudinal Field Experiment. Issue 1 (May 2017) - He, Yi; Chen, Qimei; Lee, Ruby P.; Wang, Yonggui; Pohlmann, Attila
Why do some consumers evangelize brands and create value for them even without receiving any direct reward in return? How do their motivations influence their role behaviors and their identification with the company or brand? We draw on motivation theory and the in- and extra-role literature of leadership to propose a theoretical framework. We use this framework to analyze data from one cross-sectional survey conducted with members of two online brand communities and one longitudinal field experiment with consumers of one new online brand community. We first separate community members' motivations into three types of psychological needs (self-competency, self-belongingness, self-autonomy) that are fulfilled by membership in a brand community. We investigate how each of these needs influences consumers' in-role and extra-role behaviors, which in turn positively affect their brand identification and create value for the company. Our results show that self-competency motivates both in- and extra-role behaviors, self-belongingness only increases less involved in-role behaviors, and self-autonomy only affects more involved extra-role behaviors. Both role behaviors foster beneficial consumer brand identification. We discuss how these findings can inform marketers' brand community-building strategies.